(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The study involved 44 athletes involved in various sports who had traumatic injuries to the knee/ankle joints. The main group included 44 athletes, whose comprehensive rehabilitation program included RTI. The control group consisted of 15 athletes whose rehabilitation program was carried out without the inclusion of RTI.